Runes : a concise history / Tom Birkett. - Birkett, Tom (Oxford University Press, 2025)
This is an accessible and illuminating introduction to the history of the runic script, a writing system in use in the medieval North from the Roman Iron Age until the Reformation and beyond. Runes were the only writing system known to Germanic tribes, including those who migrated to England, and they provide a first-hand account of huge social change in the medieval North, including the Viking expansion in Europe and the adoption of Christianity.